Has agricultural trade liberalization improved welfare in the least-developed countries? - Ingco, Merlinda D.; World Bank. (Washington, D.C. : World Bank, International Economics Dept., International Trade Division, 1997)
The analysis in this paper focuses on the welfare effects of agricultural price changes taking into account the trade and domestic agricultural distortions in the economy
"April 1997"--Cover.
Includes bibliographical references: p. 28-29.
osc 01/02/2019
Loans
Keywords: Agricultural industries; Free trade; Agricultural economics